ANALYSIS OF THE IMPACT TEST STRENGTH OF SQUID FIBRE-REINFORCED COMPOSITES - Fiky Firmansyah; Moh. Hartono (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study aims to determine the effect of volume fraction, fibre angle direction, and fibre length on the impact strength of squid fibre-reinforced composites. Squid fibre is a natural animal fibre that has excellent potential in the development of composite materials. The use of squid fibre as a composite reinforcement can be an alternative to reduce organic waste from marine products and produce new composite materials in sustainable manufacturing applications. The research method was conducted with quantitative experiments to determine the effect of fibre volume fraction with variations of 25%, 50%, and 75%; fibre angle direction with variations of 45° and 90°; and fibre length with variations of 20 mm, 30 mm, and 40 mm. This study used the Factorial DOE statistical data analysis method. The results showed that volume fraction and fibre length significantly affected the impact strength of the composite. The higher the volume fraction and fibre length, the higher the impact strength value of the composite. Meanwhile, the direction of fibre did not show a significant effect. The 75% volume fraction produced the highest impact strength of 0,0738 J/mm², and the 25% volume fraction produced the lowest value of 0,066 J/mm². The 45° fibre direction produced an impact strength value of 0,07098 J/mm², and the 90° fibre direction produced a value of 0,07097 J/mm². The 40 mm fibre length produced the highest impact strength value of 0,078 J/mm², and the 90° fibre direction produced a value of 0,07097 J/mm².